Peran Media Televisi dalam Edukasi Politik bagi Generasi Z - 10080021019, Fatia Nabila Wida Wijaya; Maya Amalia Oesman Palapah (Bandung Conference Series: Public Relations, 2025)
Abstract. The phenomenon of low political participation among Generation Z has raised serious concerns as it has the potential to affect the quality of democracy in Indonesia. As digital natives with fast-paced, social media–driven information consumption patterns, Generation Z requires a political communication approach that is both relevant and interactive. In response to this challenge, tvOne, through its Kabar Pemilukada program, delivers political education tailored to the communication style of younger audiences by implementing a media-based Public Relations strategy. This study aims to analyze the role of television media in enhancing political literacy among Generation Z through PR strategies applied in the Kabar Pemilukada program. The research employs a qualitative method with a case study approach to explore tvOne’s PR strategy implementation in depth. Data were collected through content observation of Kabar Pemilukada, analysis of tvOne’s official social media platforms, and interviews with the tvOne Public Relations team as well as several Generation Z informants. The findings reveal that the Kabar Pemilukada program effectively raises political awareness among Generation Z through communication strategies that leverage television as owned media combined with digital platforms. This approach proves effective as it aligns political information delivery with Generation Z’s preferences by incorporating engaging visuals, simplified language, and interactive educational content. Keywords: Political Education, Generation Z, Public Relations Abstrak. Fenomena rendahnya partisipasi politik Generasi Z menjadi perhatian serius karena berpotensi memengaruhi kualitas demokrasi di Indonesia. Sebagai generasi digital native dengan karakteristik konsumsi informasi yang cepat dan berbasis media sosial, Generasi Z membutuhkan pendekatan komunikasi politik yang relevan dan interaktif. Untuk menjawab tantangan tersebut, tvOne melalui program Kabar Pemilukada menghadirkan edukasi politik yang dikemas sesuai dengan gaya komunikasi generasi muda dengan menerapkan strategi Public Relations berbasis media. Penelitian ini bertujuan untuk menganalisis peran media televisi dalam meningkatkan literasi politik Generasi Z melalui strategi PR yang diterapkan pada program Kabar Pemilukada. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan studi kasus untuk menggali implementasi strategi PR tvOne secara mendalam. Pengumpulan data dilakukan melalui observasi konten Kabar Pemilukada, analisis media sosial resmi tvOne, serta wawancara dengan tim Public Relations tvOne dan beberapa informan Generasi Z. Hasil penelitian menunjukkan bahwa program Kabar Pemilukada mampu meningkatkan kesadaran politik Generasi Z melalui strategi komunikasi yang menekankan pemanfaatan media televisi sebagai owned media yang dipadukan dengan platform digital. Pendekatan ini dinilai efektif karena menyesuaikan penyajian informasi politik dengan preferensi Generasi Z melalui visual yang menarik, bahasa yang sederhana, dan konten edukatif yang interaktif. Kata Kunci: Edukasi Politik, Generasi Z, Public Relations